Effect of coil diameter on the performance of interior and embedded permanent magnet for double-stator generator - Ibrahim, Nur Amira; Misron, Norhisam; Hairulnizam, Hairul Faizi; Vaithilingam, Chockalingam Aravind; Nashiren, Farzilah Mailah; Aris, Ishak (Universiti Putra Malaysia Press, 2025)
The permanent magnet synchronous motor (PMSM) intended for low-speed, high-torque applications generally possesses a substantial physical size, and the internal space of the permanent magnet rotor is frequently underutilized. The rising electrical demands in electric machines have necessitated enhancements in power density, especially in double-stator systems featuring interior and embedded permanent magnets. Nevertheless, research on motors employing copper coils of differing sizes is restricted. This paper analyses the performance of an interior and embedded permanent magnet double-stator generator using JMAG software by varying the coil diameter, establishing an inverse proportionality between coil diameter and the number of turns per slot. Performance analysis under different loads and speeds showed that a 1.0 mm coil diameter achieved the highest average power (293W) at 2 ohms for speeds of 200 rpm and 1662 W at 1 ohms for 800 rpm. Larger diameters did not guarantee higher output; 0.75 mm and 1.0 mm were the best performers. A 1.0 mm coil also exhibited the best power efficiency (56%–75%) across all speeds, outperforming 0.5 mm (below 55% efficiency) and 1.5 mm (efficiency above 73% but with a steep slope in load resistance variation).